Synthesis and antiviral activity of scopadulcic acids analogues (2003)
ABSTRACT: The synthesis and antiviral properties of several scopadulcic acid analogues functionalized at C-6/C-7 and C-13 is reported. The preparation of advanced intermediates for the synthesis of scopadulcic acid B/scopadulciol analogues is also described. The biological study revealed the importance of polar groups at C-13, while the stereochemistry at C-8 was not critical for activity.